Satellite Remote Sensing Reveals More Beneficial Effect of Forest Plant Diversity on Drought Resistance in More Arid Areas of Yunnan, China - Guotao Ma; Hao Sun; Keke Hu; Hong Zhou (Ecology and Evolution, 2025)
ABSTRACT Plant diversity is important in enhancing an ecosystem's drought resistance. However, the relationship between plant diversity and drought resistance has historically aroused much controversy. Given that most previous studies on the relationship were conducted with in situ data at a small or point scale, this study explored the relationship with satellite remote sensing, taking Yunnan Province of China as the study area. Specifically, Sentinel‐2 remote sensing data were used to estimate plant diversity. The temporal correlation between the standardized vegetation index (SVI) and standardized precipitation evapotranspiration index (SPEI) was used to express the vegetation sensitivity to drought or drought resistance. A moving window method was developed to explore the relationship between plant diversity and drought resistance. MODIS and SPEI data from 2000 to 2018, as well as Meteorological reanalysis data from 1990 to 2020, were utilized. Results indicated that (1) the remotely sensed plant diversity index was found significantly correlated with field investigations of plant diversity in the study area, with a correlation coefficient of around 0.43–0.49 and p‐value < 0.001. The plant diversity of the study area can be recognized with the Sentinel‐2 remote sensing data. (2) The area proportion of having positive temporal correlation coefficients between SVIs and one‐month SPEI varied around 60%–88% during the dry seasons, while that varied around 30%–50% during the wet seasons. Most of the forest vegetation in the study area was sensitive to drought in the dry seasons rather than in the wet seasons. (3) About 80% of the study area presented a beneficial effect of plant diversity on drought resistance, that is, the higher the plant diversity, the lower the forest sensitivity to drought. (4) The beneficial effect of plant diversity has different manifestations in different regions, and it was stronger in more arid and drought‐prone areas.